Gliding motility in Myxococcus xanthus: mgl locus, RNA, and predicted protein products. - Stephens, K (1989)
Mutants of Myxococcus xanthus that had lost the ability to glide were examined to elucidate the mechanism of gliding motility. Nonmotile mutants resulting from a single mutational step were all defective at the same locus, mgl, which implied an important role for the mgl product(s) in gliding. Deletion experiments, transposon insertion mutagenesis, and genetic rescue of mgl mutants mapped the locus to a 1.6-kilobase segment of Myxococcus DNA. Two species of RNA that hybridized with mgl DNA were found both during vegetative growth and during the starvation-induced development of fruiting bodies, which also requires cell movement. The two RNA species, of 1.5 and 1.3 kilobases, had the same 5' to 3' orientation and overlapped extensively. The DNA sequences of mgl+ and of seven mgl mutants were determined. Each mutant differed from mgl+ by a single-base-pair change in the sequence. Two adjacent open reading frames were found in the sequence hybridizing to both species of mgl RNA. Six of the single-base-pair changes, each of which would result in a single-amino-acid change, and an insertion-produced mgl mutation were located in the downstream open reading frame. This open reading frame (of 195 amino acids) is therefore an mgl gene, called mglA. The function of the upstream open reading frame is not known with certainty, although it does contain one of the mgl mutant sites and could be a second mgl gene.